Proceso de atención de enfermería en adolescente de 13 años de edad con apendicitis aguda. - Endara Aguilar, Erick Patricio (2021)
An infectious inflammatory disease of the cecal appendix, or by its most common name called this pathology, acute appendicitis a picture that presents about a third of the causes of acute abdominal pain condition in people who go to emergency services, the sac-shaped appendix is an organ of involution, tubular, blind-terminated tissue that measures 7 to 6 cm in length and about 3 to 4 mm wide , presenting its implantation base under the ileus-cecal valve in the large intestine, at the junction of the colon depending on the location of the blind. The tip of it being variable, reveals the different forms of exposure; internal latero-cecal, external latero-cecal, retrocecal and retromesenteric. The primary objective of this case study is to employ the nursing care process in a adolescent patient diagnosed with acute appendicitis. A certain pathology, describing its main symptomatology, abdominal pain lacking in all patients due to the position of the cecal appendix usually in epigastrium, associated with fever, nausea, vomiting, pain to palpation in the right iliac pit and leukocytosis. However, its diagnosis is purely clinical, accompanied by a well-developed medical history and a physical examination since said pathology table can occur atypically mainly in children, pregnant women and the elderly, so it is of the utmost importance to know widely the anatomy, pathipathology, clinical picture, complementary examinations, with their respective stage of suffering in order to rule out a differential diagnosis.